Leader-Following Consensus of Multi-agent in Switching Networks with Time-Delay - Hui Yu; Gaoyang Liu; Yi Zhang (Institute of Advanced Engineering and Science, 2013)
This paper is devoted to the study of multi-agent consensus with a time-varying reference state in directed networks with both switching topology and constant time delay. Stability analysis is performed based on a proposed Lyapunov–Krasovskii function. Sufficient conditions based on linear matrix inequalities (LMIs) are given to guarantee multi-agent consensus on a time-vary reference state under arbitrary switching of the network topology even if the network communication is affected by time delay. Finally, simulation examples are given to validate the theoretical results. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2603